Profile Of Waiting Time For Compounded And Non-Combounded Prescription Services At Siko Community Health Center, North Ternate District - Ihsan, Ikhlashul; Yuyun Wirasasmita; Sarni (International Journal of Multidisciplinary Learners, 2024)
Pharmaceutical services have direct responsibility to patients related to the provision of pharmaceuticals, aiming to significantly improve the quality of life of patients. In order to meet the demands of society for quality of service, a change is needed from the old image, which focuses on finished drug products, to a patient-oriented image, known as the philosophy of pharmaceutical service.The purpose of this study is to find out how long it will take to be prescriptive and non-toxic in the north ternate district district to review from 2016’s no.27 permenkes. In the study a quantitative descriptive method with a nonlinear perspective was used, descriptive observation was made. The study was conducted in the siko district district of north ternate district with 94 respondents. As a result of this study, the average wait time for prescription drug services was 6.2 minutes and a prescription drug was 12.56 minutes. The ministry of raw materials at ≤ o has been able to meet the appropriate standards of farification, the length of time expected by the Indonesian ministry of health no. 72 year 2016 to be defined as "drug-prescribed" time .